2015
DOI: 10.1037/a0038915
|View full text |Cite
|
Sign up to set email alerts
|

Disgust sensitivity predicts defensive responding to mortality salience.

Abstract: Disgust protects the physical self. The present authors suggest that disgust also contributes to the protection of the psychological self by fostering stronger defensive reactions to existential concerns. To test this idea, 3 studies examined the link between disgust sensitivity and defensive responses to mortality salience or "terror management" processes (Greenberg, Solomon, & Pyszczynski, 1997). Each study included an individual difference measure of disgust sensitivity, a manipulation of mortality salience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…With respect to intertemporal decision making, the effects of disgust are understudied and mostly unknown. To the best of our knowledge, the only study investigating the effect of disgust on temporal discounting indicated that disgust sensitivity predicted a preference for larger later rewards [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to intertemporal decision making, the effects of disgust are understudied and mostly unknown. To the best of our knowledge, the only study investigating the effect of disgust on temporal discounting indicated that disgust sensitivity predicted a preference for larger later rewards [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies of meaning-regulation vary highly (see Jonas et al, 2014) and it is possible that different affective states predict divergent meaning-regulation behavior. For example, disgust sensitivity has been shown to moderate defensive responses to mortality salience (Kelley, Crowell, Tang, Harmon-Jones, & Schmeichel, 2015). Consistently, our research suggests that disgust is inversely related to meaning search , a nondefensive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…no mask, surgical mask, cultural mask) between-participants design. Participants completed 2 To explore the possibility of individual differences in the management of death awareness after exposure to facemasks (Kelley et al, 2015;Olivera-La Rosa et al, 2020), Study 3 included a measure of disgust sensitivity (Tybur et al, 2009). In addition, because the NHS is a symbol of national identity (Stubley, 2020), and because death reminders can increase people's optimism when their national identity is salient (Dechesne et al, 2000), we further examined the possibility that exposure to cultural facemasks after death reminders will increase people's optimism.…”
Section: Methodsmentioning
confidence: 99%